Impacts of stem cells from different sources on wound healing rate in diabetic foot ulcers: a systematic review and meta-analysis - Tong, Le; Tang, Lin; Tang, Bangli; Zhang, Jianna (Frontiers in Genetics, 2025)
BackgroundDiabetic foot ulcers (DFU) are a significant complication of diabetes, with huge implications on patient morbidity and healthcare costs. The objective of this meta-analysis was to evaluate the impacts of stem cells from different sources on wound healing rate in DFU patients.MethodsWe systematically retrieved records via key databases PubMed, Cochrane Library, Web of Science, Embase, China National Knowledge Infrastructure (CNKI) and Wanfang from the inception to October 2024. The Stata 16.0 (Stata Corp, TX) software was used to perform the meta-analysis. Risk of bias in all included studies was evaluated by Cochrane Risk of Bias version 2.ResultsA total of 24 studies involving 1,321 patients were included. There was an increased likelihood of wound healing with peripheral blood-derived stem cells, the most effective cells (odds ratios (OR) = 7.31, 95% CI: 2.90–18.47), followed by adipose-derived stem cells (OR = 5.23, 95% CI: 2.76–9.90), umbilical cord-derived stem cells (OR = 4.94, 95% CI: 0.61–40.03), bone-derived stem cells (OR = 4.36, 95% CI: 2.43–7.85) and other sources stem cells (OR = 3.16, 95% CI: 1.83–5.45). Nevertheless, only umbilical cord-derived stem cells showed statistical significance (p < 0.05). The heterogeneity ranged from non-existent in the adipose and peripheral blood groups (I2 = 0.00%) to moderate in the bone groups (I2 = 26.31%) and other groups (I2 = 30.62%), and substantial in the umbilical cord groups (I2 = 88.37%). Asymmetrical funnel plots pointed to publication bias, but the trim-and-fill method to correct for this brought the effect estimates even lower: based on the pooled OR, corrected OR was 3.40 (95% CI 2.39–4.84). Stem cell therapy was also associated with improvements in several secondary outcomes, suggesting its potential to influence the progression of DFU.ConclusionOur study suggested that stem cells from different sources showed potential in promoting wound healing in DFU, although with some variation in effectiveness. Despite some publication bias and moderate heterogeneity, the overall therapeutic effect remained positive. These findings indicated that stem cell therapy might influence the progression of DFU.